Integrated Legal Protection of Women in Conflict with the Law in the Criminal Judicial Process (Decision Case Number 677/Pis.Sus/2018/PN Cbi) - Indriati Amarini; Nikmah Fitriah; Rizky Aulia Cahyadri (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: The state has an obligation to ensure that women obtain justice and are free from all discrimination in the criminal judicial process. Women in conflict with the law frequently feel uncomfortable when facing court proceedings in the position of suspect, victim, or witness. This paper analyzed legal considerations in the court decision of Bogor Cibinong District Court number 677/Pis.Sus/2018/PN Cbi.  Methodology: This research employed the doctrinal legal analysis methodology. This study aimed to analyze the legal protection of women in conflict with the law in the courtroom. This investigation could be a regulating juridical consideration with philosophical and conceptual approaches.  Results: The result of the consideration appeared that the criminal equity handled in court was full of ethical issues. Recently, there was the issuance of Supreme Court Regulation Number 3 of 2017 concerning Rules on the Hearing of Cases Including Women in Conflict with the Law. The Decision of Bogor Cibinong District Court Number 677/Pis.Sus/2018/PN Cbi managed a rapist of two children free from the charge of 14 years in prison for there is no witness who saw the rape. The integrated protection of women is required since they deal with the law during court proceedings and in the stages of inquiry, investigation, prosecution, and punishment.  Applications of this study: Regulation through legislation is required to protect women in conflict with the law in the criminal justice process.  Novelty/Originality of this study: In contrast to previous research, this research focused on studying how significant legal protection is for women in conflict with the law. Keywords: Legal Protection, Women, Litigation   ABSTRAK  Tujuan: Negara memiliki kewajiban untuk memastikan perempuan memperoleh keadilan dan bebas dari segala diskriminasi dalam proses peradilan pidana. Perempuan yang berkonflik dengan hukum seringkali merasa tidak nyaman ketika menghadapi proses peradilan dalam posisi sebagai tersangka, korban, atau saksi. Artikel ini bertujuan untuk menganalisis pertimbangan hukum dalam putusan Pengadilan Negeri Bogor Cibinong nomor 677/Pis.Sus/2018/PN Cbi.  Metodologi: Penelitian ini menggunakan metodologi analisis hukum doktrinal. Penelitian ini bertujuan untuk menganalisis perlindungan hukum terhadap perempuan yang berkonflik dengan hukum di ruang sidang. Investigasi tersebut menjadi pertimbangan yuridis dengan pendekatan filosofis dan konseptual.  Hasil: Dari hasil penelitian ditemukan bahwa peradilan pidana yang ditangani di pengadilan sarat dengan persoalan etik. Baru-baru ini, telah diterbitkan Peraturan Mahkamah Agung Nomor 3 Tahun 2017 Tentang Pedoman Mengadili Perkara Perempuan Berhadapan dengan Hukum. Putusan Pengadilan Negeri Bogor Cibinong Nomor 677/Pis.Sus/2018/PN Cbi membebaskan pemerkosa dua anak dari dakwaan 14 tahun penjara karena tidak ada saksi yang melihat pemerkosaan tersebut. Perlindungan terpadu terhadap perempuan diperlukan karena mereka berhadapan dengan hukum selama proses peradilan dan pada tahap penyelidikan, penyidikan, penuntutan, dan hukuman.  Aplikasi penelitian ini: Pengaturan melalui peraturan perundang-undangan diperlukan untuk melindungi perempuan yang berkonflik dengan hukum dalam proses peradilan pidana.  Kebaruan/Orisinalitas: Berbeda dengan penelitian sebelumnya, penelitian ini berfokus untuk mengkaji seberapa signifikan perlindungan hukum bagi perempuan yang berkonflik dengan hukum.  Kata kunci: Perlindungan Hukum, Perempuan, Litigasi